Renal Failure—Measuring the Glomerular Filtration Rate - Thomas, Christian (Deutscher Arzte Verlag, 2009)
BACKGROUND: Chronic renal disease is common, and its prevalence is rising. Its main causes are hypertension and diabetes mellitus. An abnormally low glomerular filtration rate (GFR) often escapes medical notice in the earliest, most treatable stage, so that an increasing number of patients progress to end-stage renal failure. Early recognition of low GFR would thus be an important clinical advance. METHODS: The authors selectively review the literature retrieved by a PubMed search on the topic and also present their own clinical and laboratory data. RESULTS: Chronic renal failure can be detected early by direct measurement of the GFR with the aid of an exogenous filtration marker. Such techniques are costly and time-consuming and are therefore indicated only for patients at special risk. Chronic renal disease can also be diagnosed early with the aid of the endogenous filtration markers creatinine and cystatin C, which serve as indicators of a low GFR. The serum levels of these two substances are not taken as measures of GFR in themselves, but are rather entered into predictive equations for the estimation of GFR. Cystatin C-based equations seem to be more sensitive indicators of low GFR than creatinine-based equations. CONCLUSIONS: Creatinine- and cystatin C-based equations for the estimation of GFR are valuable tools for the early diagnosis of chronic renal disease and for disease staging according to the US National Kidney Foundation criteria.